MCDA: análise de decisão multicritério como ferramenta de avaliação de instalações portuárias: o caso dos terminais de contêineres brasileiros - Xavier, Carlos Guimarães (2009)
This paper attempts to assess, with support from MCDA methodology – multi-criteria decision analysis, the Brazilian container terminals on its potential as vectors of growth of the economy in the medium and long-term for prioritization of public and private investments. The work is embodied in a bibliography of the subject decision, which serves as a base, followed by a study of the subject port, in order to find the factors that make feasible the flowering and development of a port site, further to seek trends in the sector of Brazilian container terminals. After these steps, a model is developed to solve the problem of evaluation of terminals with aid of the software Expert Choice. The results point to a significant change of paradigm in the national port scenario in the future. Ports that are now listed at the top of the ranking of container handling statistics may not have sufficient space to expand, while others that are less vigorous, can flourish in the coming decades, due to site characteristics of each port. The most relevant criteria were selected as the model was developed, these are: sheltered waters, back areas, access through land and sea, dealing with environmental issues, strategic location, regional vocation, extension of quays and areas of expansion. Among findings of this study, one can cite: 1 - The Port of Santos, traditional leader of the national ranking in handling of containers should be maintained at the first team, thanks to its proximity to the main national industrial and economic center, the region of Greater São Paulo. However, it is close to its capacity of the operational limit, with areas of expansion, as the project Barnabé-Bagres. 2 - Another port that stood out in the final classification was Itaguaí, already today with increased movement and huge potential for growth in the container activities. It has excellent condition of sheltered waters, good strategic location, between Rio de Janeiro and Sao Paulo, two economic poles, with influence on the national scene, and has a consistent expansion plan, especially related to the increase in containers.